Mother-to-child transmission of HIV and its predictors among HIV-exposed infants at Bamenda Regional Hospital, Cameroon - Victor N. Fondoh; Njong A. Mom (AOSIS, 2017)
Background: Mother-to-child transmission (MTCT) of HIV, has been a major global public health burden. Despite the use of antiretroviral prophylaxis by HIV-positive pregnant women and their infants, safe obstetric practice and safe infant feeding habits in the prevention of MTCT of HIV, the prevalence of HIV among HIV-exposed infants is still high in Cameroon. Objective: Our objectives were to determine the prevalence, assess the predictors and determine the effect of combination antiretroviral therapy (cART) on MTCT of HIV at the regional hospital in Bamenda, Cameroon. Methods: This was a retrospective study. Secondary data from 877 HIV-exposed infants aged ≤ 72 weeks were extracted from the records between January 2008 and December 2014. The predictors and effect of cART on MTCT of HIV were analysed using a multivariable logistic regression model and risk analysis, respectively. Results: Out of 877 HIV-exposed infants, 62 were positive for HIV, giving a prevalence of 7.1%. Maternal antiretroviral intervention and infant age group were statistically significant predictors of MTCT of HIV. HIV-positive mothers who were on cART were 2.49 times less likely to transmit HIV than those who were not on cART. Conclusion: In order to reduce the prevalence of HIV among HIV-exposed infants, maternal antiretroviral intervention should be targeted and the use of cART by HIV-positive pregnant women should be encouraged.